Components of a Successful Model for Economic Empowerment of Rural Youth - Anjani Kumar and Rashmi Singh, (Indian Journal of Extension Education, 2014)
Entrepreneurship development has been recognized essential factor, playing great role in agricultural sector in the era ofLiberalization, Privatization and Globalization, open competition and free market economy. Agro-basedentrepreneurship activities among farmers, farm women and rural youth are vital in the context of generating gainfulemployment, minimizing the regional disparities and development of socio economic condition. However, rural youthlack in entrepreneurial traits like ability to identify opportunities (Satapathy and Mishra, 2011). It is necessary that ruralyouth are mobilized to go for entrepreneurship activities as per their resources and market demand of the area, many youthare interested to undertake such activities to earning, but the major problems faced by them are usually lack of skill,financial support during establishment and finally marketing of the produce.Such entrepreneurship development amongrural youth can play a vital role in generating self employment there by reducing the unemployment, checking migrationfrom rural areas, batter use of locally available resources, balance regional disparities and reducing unrest among youth.Kumar et.al. (2012) observed that through the network of KVKs lakhs of people are trained in vario us areas.Thus KVKscan play a crucial role in promoting entrepreneurship among rural youth through customized trainings. As a part of studyof entrepreneurship development among rural youth of Gurgaon district in Haryana, Krishi Vigyan Kendra started a longduration vocational programmes for rural youth & women science 1999. It is heartening to say that since then the KVK hasnot looked back and had been organizing need based training course having potential for additional income andemployment generation and fitting well into eco-socio-cultural and technological system of their project area. Such needbased, standardized and well-planned course were conducted by KVK from 2000 to 2014 a period of 15 years. Theeffectiveness of these training programmes assessed through evaluation and interaction with the farmers from time to timeand found quit an encouraging impact. Amongst the vocational course conducted at KVK, the Dairy farming, Beekeeping,Dress designing & tailoring, Preservation of seasonal fruits and vegetables, custom service in Plant protection, Motorwinding and tractor repairing were found to be extremely popular and the overall adoption rate is 470. %. This experiencevery strongly highlights the need for entrepreneurship development for self-empowerment to the rural youth andstrengthening the rural youth economy.